Antecedents of Advertising Value to Brand Awareness and Subscription Intention (Case of Disney+ Hotstar Ads on Youtube Ads) - Novia Felicia Gozali; Pujianto Yugopuspito (Enrichment : Journal of Management, 2021)
Each advertisement that is displayed has its own value (advertising value) for the audience which can be in the form of entertainment, informativeness, customization and irritation. With these four elements in an advertisement, it is hoped that the advertisement will further increase brand awareness and subscription intention. This study was conducted to determine the relationship between the variables of entertainment, informativeness, customization and irritation, advertising value, brand awareness & subscription intention. Based on the results of data analysis that has been carried out, it is concluded that, first, entertainment has a positive influence on advertising value. Second, informativeness has a positive effect on advertising value. Third, customization has a positive effect on advertising value. Fourth, irritation does not have a significant negative effect on advertising value. Fifth, advertising value has a positive influence on subscription intention. Sixth, advertising value has a positive influence on brand awareness. Seventh, brand awareness has a positive influence on subscription intention.